KESANTUNAN BERBAHASA DALAM TINDAK TUTUR SISWA KELAS XI.5 SMA NEGERI 1 KUBUNG PADA PEMBELAJARAN TEKS DRAMA - Bellya Darma Sari; Ermawati Arief; Ena Noveria; Herlin Triana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: This study aims to describe the observance and violation of the ten politeness maxims and the speech context of grade XI.5 students of SMA Negeri 1 Kubung in drama text learning. This is qualitative research using a descriptive method. The data consist of students’ utterances collected through direct observation over three meetings, then recorded and transcribed. The data were analyzed using Leech’s (2014) ten politeness maxims and Hymes’ (1974) SPEAKING context theory. The observation yielded 30 relevant utterances. The results show that all ten maxims appeared in students’ speech acts, in both observance and violation. The tendency leaned toward observance, namely 20 data (66.7%), while violations accounted for 10 data (33.3%) and generally occurred in informal interactions with peers. It is concluded that drama text learning is an effective space for developing students’ ability to speak politely.Keywords: Pragmatics, Leech’s Maxims, Maxim Observance, Maxim Violation, Speech Context